THE EFFECT ANALYSIS OF MACRO-ECONOMIC VARIABLES TOWARD INDONESIAN ISLAMIC STOCKS RETURN - Muhammad Zilal Hamzah; Tubagus Irmansah; Isnaini Mukti Azis (Indonesian Management and Accounting Research, 2014)
This study aims to determine the effect of macroeconomic variables on returns of Indonesian Islamic stocks (Jakarta Islamic Index). The sample data uses are returns of the Islamic stock index from 2005:01 - 2010:04. This study uses Ordinary Least Square (OLS) method and the application of panel data to assess the existence of any effect of the macroeconomic variables on stock returns of the Indonesian Islamic stocks. The results of this study exhibit that the Islamic stock returns are significant simultaneously, but insignificant partially.Keywords: macroeconomic variables, Islamic stock returns